A Comparison of Game-Based Learning and Think-Pair-Share on Grade 8 Students’ Learning Achievement at SMP Katolik Budi Murni 1 - Medianti Simanjuntak (Pustaka Karya Mandiri, 2026)
Game-Based Learning and Think-Pair-Share are two active learning models that can be used to improve students’ participation and learning achievement. Game-Based Learning emphasizes challenge, interaction, feedback, motivation, and learning through game-like activities, while Think-Pair-Share emphasizes individual thinking, peer discussion, and classroom sharing. This study compared the effect of Game-Based Learning and Think-Pair-Share on Grade 8 students’ learning achievement at SMP Katolik Budi Murni 1. The study employed a pretest-posttest non-equivalent control group design. The population consisted of all Grade 8 students at SMP Katolik Budi Murni 1, with a total population of 242 students. The sample consisted of Grade 8C as the experimental group taught through Game-Based Learning and Grade 8E as the comparison group taught through Think-Pair-Share. The experimental group consisted of 28 students, while the comparison group consisted of 29 students. Data were collected through achievement tests administered before and after the instructional treatment. The data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, gain-score analysis, and effect size interpretation. The results showed that both groups improved after instruction. However, the Game-Based Learning group achieved a higher mean gain than the Think-Pair-Share group. The Game-Based Learning group improved from a pretest mean of 61.36 to a posttest mean of 84.39, with a mean gain of 23.04. The Think-Pair-Share group improved from a pretest mean of 60.66 to a posttest mean of 77.48, with a mean gain of 16.83. The gain-score comparison showed a statistically significant advantage for Game-Based Learning. The study concludes that Game-Based Learning was more effective than Think-Pair-Share in improving Grade 8 students’ learning achievement in the observed instructional context.